The feasibility of an augment reality system to study the psychophysiological correlates of fear‐related responses. Issue 9 (22nd August 2018) - Brás, Susana; Soares, Sandra C.; Cruz, Telmo; Magalhães, Tiago; Marques, Bernardo; Dantas, Cláudia; Fernandes, Nuno; Fernandes, José Maria
Abstract: Background: Previous studies have successfully used augmented reality (AR) as an aid to exposure‐based treatments for anxiety disorders. However, to the best of our knowledge, none of these studies have measured the physiological correlates of the fear response, relying solely on self‐reports and behavioral avoidance tests. Methods: As the physiological defensive reactivity pattern impacts on the treatment effectiveness, we tested the feasibility of an AR system integrated in a mobile and wearable device for assessing the psychophysiological mechanisms (heart rate) involved in fear responses in real‐life contexts. Specific phobia was used as a model given its prototypical defensive hyperreactivity toward the feared stimulus (spiders to spider phobics, in the current study). Results: The results showed that the stimuli presented using AR were able to induce physiological alterations in the participants, which were specific depending on the stimulus type (fear or neutral) and on the participants' level of spider fear (phobic and control group). These physiological correlates of the fear response were reflected both in the intensity of heart rate (in relation to the baseline) and in the time needed to react and recover after the stimulus exposure. Finally, we tested a theoretical model that showed that the physiological responses of phobic individuals when facing their phobic stimulus only explained its own data. Conclusions: We argue in favor of the system's feasibility at capturing and quantifying the physiological dimension of fear‐related responses, which may be of great value for diagnostic and treatment purposes in anxiety disorders, namely specific phobia. Abstract : We tested the feasibility of an AR system integrated in a mobile and wearable device for assessing the psychophysiological mechanisms involved in fear responses in real‐life contexts. The stimuli were able to induce physiological alterations in the participants, which were specific depending on the stimulus type (fear or neutral) and on the participants' level of spider fear (phobic and control group), arguing in favor of the system's feasibility at capturing and quantifying the physiological dimension of fear‐related responses.